Synthesis and Antibacterial Activity of Chitosan-Cinamaldehyde/AgNp Schiff Base Composite - Huda, Muhammad Badrul; Rinaryadi, Kemilau Permata Hati; Ngadiwiyana, Ngadiwiyana; Christwardana, Marcelinus; Sarjono, Purbowatiningrum Ria; Ismiyarto, Ismiyarto (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2025)
Chitosan is a material that has antibacterial properties. Chitosan was modified with cinnamaldehyde to form chitosan Schiff base, which acts as a capping agent in the synthesis of silver nanoparticles. The Schiff base product was modified again into a silver nanoparticle Schiff base composite to improve its ability as a capping agent and improve its antibacterial properties. This study aims to synthesize a chitosan-cinnamaldehyde/AgNP Schiff base composite (CCSB/AgNP) as an active ingredient with excellent antibacterial properties. The first stage was the synthesis of a chitosan-cinnamaldehyde Schiff base. In the second stage, the synthesis of the chitosan/AgNP composite was carried out by adding STPP with sonication and a water bath. The third stage involved synthesizing of the CCSB/AgNP composite using the same method as the second stage employing both heating and non-heating as well as sonication and non-sonication. The product was characterized using a UV-Vis spectrophotometer, FT-IR, SEM-EDX, mapping, and AAS. Antibacterial tests were performed on the synthesized product using the Total Plate Count (TPC) method. Chitosan has a molecular weight of 338080 g/mol and a degree of deacetylation of 65.09%. The Schiff base product of chitosan-cinnamaldehyde is a brownish-yellow solid with a yield of 76.9% (w/w) and a degree of substitution of 87.02%. The presence of Ag was confirmed by EDX mapping, which revealed mass percentages of 0.26%, 1.00%, and 3.97% for C/AgNP-1, C/AgNP-2, and CCSB/AgNP-2, respectively. The chitosan/AgNP product has a yield of 97% (w/w) and an SPR effect at 439 nm. The synthesis of CCSB/AgNP obtained a dark green solid with a yield of 87% (w/w) and an SPR effect at 433 nm. The antibacterial activity test yielded the highest percentage reduction in the number of bacteria in CCSB/AgNP at 3 days of observation at 95.1%, and 7 days at 94.1%.